Rural Development from a Territorial Perspective : Lessons and Potential in Sub-Saharan Africa - Quan, Julian (Washington, DC: World Bank, 2012)
Sub-Saharan Africa's (SSA) poverty reduction and economic growth strategies and programs concentrate on consolidating economic growth at the macro level, through increased investment and productivity of key sectors including agriculture and enhanced employment. Such strategies do not set out clear mechanisms whereby prosperity can be generated at the sub-national level, nor do they recognize the different contributions that agriculture has to make to reduction of poverty in diverse locations, settings and territories. The paper analyzes the lessons and potential poverty impacts involved in the application of territorial and local economic development (LED) approaches and makes preliminary assessments of the transferability of these approaches to SSA.